2020
DOI: 10.3390/antibiotics9020042
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Campylobacter spp. Isolated from Poultry in KwaZulu-Natal, South Africa

Abstract: This study investigated the antibiotic resistance, virulence profiles, and clonality of Campylobacter jejuni and Campylobacter coli isolated from an intensive poultry farming system in KwaZulu-Natal, South Africa. Following ethical approval, samples were collected over six weeks using the farm-to-fork approach. Campylobacter spp. were identified using culture, confirmed and differentiated to species level by PCR, and subjected to antibiotic susceptibility testing. Selected antibiotic resistance (and mutations)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 34 publications
9
20
0
Order By: Relevance
“…cad F seems to be a prerequisite for the invasion of epithelial cells by any bacterial pathogen ( Ramires et al, 2020 ). The outer membrane phospholipase A ( pld A) was observed more in C. jejuni than in C. coli ( Figure 2 ), which corroborates the study in South Africa ( Pillay et al, 2020 ), while for cia B, our findings are above those of a previous report in Korea ( Oh et al, 2017 ) and contrast with the study in South Africa ( Pillay et al, 2020 ). The presence of cad F and cia B facilitates the adhesion and internalization of Campylobacter in cellular models ( Ramires et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…cad F seems to be a prerequisite for the invasion of epithelial cells by any bacterial pathogen ( Ramires et al, 2020 ). The outer membrane phospholipase A ( pld A) was observed more in C. jejuni than in C. coli ( Figure 2 ), which corroborates the study in South Africa ( Pillay et al, 2020 ), while for cia B, our findings are above those of a previous report in Korea ( Oh et al, 2017 ) and contrast with the study in South Africa ( Pillay et al, 2020 ). The presence of cad F and cia B facilitates the adhesion and internalization of Campylobacter in cellular models ( Ramires et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, cst II, cdt B, fla A, cad F, and dna J were detected in all isolates. The detection rates were similar to a previous report in Korea ( Oh et al, 2017 ) but higher than those reported in South Africa and Chile ( González-Hein et al, 2013 ; Otigbu et al, 2018 ; Pillay et al, 2020 ). cad F seems to be a prerequisite for the invasion of epithelial cells by any bacterial pathogen ( Ramires et al, 2020 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Molecular investigations have been carried using a number of typing techniques including enterobacterial repetitive intergenic consensus (ERIC), random amplified polymorphic deoxyribonucleic acid (RAPD), repetitive extragenic palindromic (REP), pulse-field gel electrophoresis, and multi-locus sequence typing [ 23 , 24 , 25 , 26 , 27 ]. Recent advances have promoted the use of whole-genome sequencing and metagenomics.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, there are plenty of interesting topics about the stewardship of old and novel agents for MDR-GNB infections that are explored in the articles published in the present Special Issue. In addition, we included two papers by Pillay and colleagues and Oloso and colleagues, which deal with resistance issues in the broiler production chain, reminding us of the importance of adopting a One Health approach in global antimicrobial stewardship interventions [9,10]. Finally, we tried to look to the future with a brief narrative review on the use of machine learning techniques in observational studies of MDR-GNB infections in humans [11].…”
mentioning
confidence: 99%